1998
DOI: 10.4278/0890-1171-12.4.237
|View full text |Cite
|
Sign up to set email alerts
|

Job Strain and Health Behaviors: Results of a Prospective Study

Abstract: The effectiveness of smoking cessation may be aided by modification of structural features of the work environment, such as job decision latitude. This study is limited by the small number of subjects who were engaged in high risk behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
107
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(117 citation statements)
references
References 75 publications
9
107
1
Order By: Relevance
“…The full model has been confirmed in a minority of studies only (23)(24)(25)(26). Single components have only partially been found to be significantly related to smoking status (27)(28)(29)(30)(31)(32)(33) and, if so, more often among women than among men. Eight studies did not report any association between model components and smoking status (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: The Challenge Of Mechanisms: Health Risk Behaviormentioning
confidence: 73%
See 1 more Smart Citation
“…The full model has been confirmed in a minority of studies only (23)(24)(25)(26). Single components have only partially been found to be significantly related to smoking status (27)(28)(29)(30)(31)(32)(33) and, if so, more often among women than among men. Eight studies did not report any association between model components and smoking status (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: The Challenge Of Mechanisms: Health Risk Behaviormentioning
confidence: 73%
“…Again, most of the studies are cross-sectional (25,28,29,37,39,40,44,(47)(48)(49)(50)(51) and concern the demand-control model. Six studies are based on longitudinal data (30,45,(52)(53)(54)(55). It is of interest to note that four of the studies found at least partial support for a role of work stress in heavy alcohol consumption or alcohol dependency (52-55), particularly among men.…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…5 While some studies have found an association between high strain, 6,7 high demands, 6,8,9 low control, 3,10 and increased BMI, other studies have reported no associations between these psychosocial characteristics of the work environment and BMI, [11][12][13][14] and, in some samples, high strain or low control were associated with lower BMI. 15,16 Associations of job strain and its components with BMI have been found to vary by sex, but not in a consistent manner 17 and stress has also been proposed to be linked with BMI beyond the work context.…”
Section: Introductionmentioning
confidence: 94%
“…This might explain, in part, the mechanism underpinning the interactive effects proposed by Kivimäki et al (J Occup Health 2010; 52: 66-73) Key words: Body mass index, Hyperphagia, Obesity, Psychological stress When stressed, some people lose and other people gain weight 1) . Although some studies have found associations between stressful work environments and increased body mass index (BMI) [2][3][4][5][6][7] , others have reported no associations between these variables [8][9][10][11][12][13] . Moreover, a highly stressful work environment was associated with low BMIs in several samples 14,15) .…”
mentioning
confidence: 99%